The Influence of System Quality and Information Quality on E-Puskesmas User Satisfaction: An Empirical Study at Kumai Community Health Center - Herlina Afrelina; Tria Saras Pertiwi; Hosizah Markam; Witri Zuama Qomarania (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The implementation of Electronic Medical Records (EMR) in primary healthcare facilities has become a critical component of Indonesia's national digital health transformation agenda. This study examines the influence of system quality and information quality on E-Puskesmas user satisfaction at Kumai Community Health Center in Central Kalimantan Province, Indonesia. Employing a quantitative research approach with cross-sectional design, data were collected from all 58 healthcare staff who directly used the E-Puskesmas system through a validated questionnaire adapted from the DeLone and McLean IS Success Model and End User Computing Satisfaction (EUCS) framework. Multiple linear regression analysis revealed that both system quality (β = 0.408, p = 0.000) and information quality (β = 0.574, p = 0.000) significantly and positively affected user satisfaction, with information quality demonstrating stronger influence. The model achieved an adjusted R² of 0.586, indicating that 58.6% of variance in user satisfaction was explained by these two variables. Descriptive analysis uncovered dimensional heterogeneity, with security and relevance achieving high categories while system reliability, timeliness, and overall satisfaction remained in moderate classification. These findings suggest that healthcare professionals in resource-constrained settings prioritize accurate and relevant patient data over technical system performance, yet infrastructure limitations continue to undermine holistic user experience. The study contributes empirical evidence for improving E-Puskesmas implementation and supports Indonesia's broader digital health integration through the Satusehat platform.